Perancangan Basis Data dan Layanan Akses Berbasis Service Oriented Architecture (SOA) Untuk Dinas Kesehatan Kabupaten Sleman - Tarigan S, Inna Yoana Sari; Soedjatmiko, Soedjatmiko; Hartanto, Rudy (Jurnal Buana Informatika, 2010)
Abstract. Database Design and Service Oriented Architecture (SOA)-based Access Service for Health Center Transactional Data on Health Office of Sleman District. Health Office of Sleman District is the regional institution that is responsible for organizing health services in the area of Sleman District. In performing these duties and responsibilities, Health Office of Sleman District requires health data and information that is accurate, precise and quick to assist policy decision making process and the health sector by leveraging communication and information technology. This research aims to design a database and SOA-based access service for transactional data center on Health Office of Sleman District. Expected, the results of this research can help Health Office of Sleman District in monitoring public health and to establish interoperability with systems from agencies or other institution.Keywords: Health Office of Sleman District, database, SOA, web service.Abstrak. Dinas Kesehatan Kabupaten Sleman adalah lembaga regional yang bertanggung jawab untuk mengatur pelayanan kesehatan di wilayah Kabupaten Sleman. Dalam melaksanakan tugas dan tanggung jawabnya, Dinas Kesehatan Kabupaten Sleman memerlukan data kesehatan dan informasi yang akurat, tepat dan cepat untuk membantu proses pengambilan keputusan kebijakan dan sektor kesehatan dengan memanfaatkan teknologi komunikasi dan informasi. Penelitian ini bertujuan untuk merancang sebuah basis data dan layanan akses berbasis SOA untuk pusat data transaksional pada Dinas Kesehatan Kabupaten Sleman. Diharapkan, hasil penelitian ini dapat membantu Dinas Kesehatan Kabupaten Sleman dalam memantau kesehatan masyarakat dan untuk membangun interoperabilitas dengan sistem dari instansi atau lembaga lain.Kata kunci: Dinas Kesehatan Kabupaten Sleman, basis data, SOA, layanan web.